Confocal analysis of cholinergic and dopaminergic inputs onto pyramidal cells in the prefrontal cortex of rodents - Zhang, Zi-Wei; Burke, Mark W.; Calakos, Nicole; Beaulieu, Jean-Martin; Vaucher, Elvire (Frontiers in Neuroanatomy, 2010)
Cholinergic and dopaminergic projections to the rat medial prefrontal cortex (mPFC) are both involved in cognitive functions including attention. These neuronal systems modulate mPFC neuronal activity mainly through diffuse transmission. In order to better understand the anatomical level of influence of these systems, confocal microscopy with triple fluorescent immunolabeling was used in three subregions of the mPFC of rats and Drd1a-tdTomato/Drd2-EGFP transgenic mice. The zone of interaction was defined as a reciprocal microproximity between dopaminergic and cholinergic axonal segments as well as pyramidal neurons. The density of varicosities, along these segments was considered as a possible activity-dependant morphological feature. The percentage of cholinergic and dopaminergic fibers in microproximity ranged from 12 to 40% depending on the layer and mPFC subregion. The cholinergic system appeared to have more influence on dopaminergic fibers since a larger proportion of the dopaminergic fibers were within microproximity to cholinergic fibers. The density of both cholinergic and dopaminergic varicosities was significantly elevated within microproximities.The main results indicate that the cholinergic and dopaminergic systems converge on pyramidal cells in mPFC particularly in the layer V. In transgenic mice 93% of the pyramidal cells expressed the transgenic marker for d2r expression, but only 22% expressed the maker for d1ar expression. Data presented here suggest that the modulation of mPFC by dopaminergic fibers would be mostly inhibitory and localized at the output level whereas the cholinergic modulation would be exerted at the input and output level both through direct interaction with pyramidal cells and dopaminergic fibers.